Political Branding of Gus Barra as Deputy Regent of Mojokerto from the Santri Community: A Content Analysis of the Instagram Feed @gusbarra_ - Ahmad Syaid Kokalo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the political branding of Gus Barra (Dr. H. Muhammad Al Barra, Lc., M.Hum.) as Deputy Regent of Mojokerto representing the santri (Islamic boarding school) community through content analysis of his Instagram account @gusbarra_. In an increasingly digital era, social media has become a pivotal instrument in political communication and the construction of public leaders' images. Gus Barra, as the son of a prominent kiai and an alumnus of Al-Azhar University in Cairo, leverages Instagram to build a political identity grounded in pesantren (Islamic boarding school) values. This research employs a qualitative approach with content analysis method applied to the Instagram feed @gusbarra_ uploaded between October 2022 and September 2023. Findings reveal that Gus Barra's political branding is constructed through three primary dimensions: (1) personality reflecting santri character, (2) appearance embodying Islamic identity, and (3) key political messages rooted in da'wah values and public service. The @gusbarra_ Instagram account presents memorable, meaningful, and engaging content consisting of highlights, reels, photos, and high-quality captions. This strategy successfully builds a positive image of Gus Barra as a young leader from the pesantren milieu who is inclusive, aspirational, and close to the people. This study is expected to serve as an academic contribution to the study of social media-based political communication in Indonesia.